How discord underlies the noise resilience of quantum illumination. (18th April 2016) - Weedbrook, Christian; Pirandola, Stefano; Thompson, Jayne; Vedral, Vlatko; Gu, Mile
Abstract: The benefits of entanglement can outlast entanglement itself. In quantum illumination, entanglement is employed to better detect reflecting objects in environments so noisy that all entanglement is destroyed. Here, we show that quantum discord—a more resilient form of quantum correlations—explains the resilience of quantum illumination. We introduce a quantitative relation between the performance gain in quantum illumination and the amount of discord used to encode information about the presence or absence of a reflecting object. This highlights discords role preserving the benefits of entanglement in entanglement breaking noise.